Performance of foamed concrete arch tile as permenent formwork for upper floor SLAB - Mohamad Zuhairi, Zulkifli (2015)
Permanent formwork is chosen to reducing waste in construction as a solution that has benefit compared to the conventional method that using scaffolding for temporary support formwork. Other than that, this research presents the lightweight arch pan to adequate the capability of arch pan serve as permanent formwork for upper floor slab which more lightly than a normal concrete. In conjunction, the scope of this research emphasize more on designing the structure and investigate the adequacy on load application that including beam, arch pan and slab for producing upper floor slab. The slab was tested to failure under three point loading. The result obtained shows the formation continues cracking line appeared indicate that particular slab act as composite structure.